The Effect of Person Organization Fit, Job Embeddedness, and Organizational Commitments on Organizational Citizenship Behavior at Citilink Indonesia Airlines - Endri Haryati; Budiyanto; Suwitho (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of: Person Organization Fit on Job Embeddedness, Person Organization Fit on organizational commitment, Job Embeddedness on Organizational Citizenship Behavior, Organizational commitment on Organizational Citizenship Behavior, etc. The population in this study were flight attendants who worked for Citilink Indonesia Airlines that met the criteria in order to obtain a homogeneous population. The sample of this study came from a representative flight attendant population (representing) as many as 151 flight attendants. The sampling technique in this study was probability sampling. The results of this study are Person Organization Fit has a significant effect on Job Embeddedness, Person Organization Fit has a significant effect on organizational commitment, Job Embeddedness has a significant effect on Organizational Citizenship Behavior, Organizational commitment has a significant effect on Organizational Citizenship.